Catalytic performance of ZrO2 and TiO2 supported copper catalysts for NOx reduction in the presence of oxygen - Saidina Amin, Nor Aishah; Tan , Eng Fong; Abdul Manan, Zainuddin (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
The catalytic reduction of NOx, using copper modified zirconia (ZrO2) and titania (TiO2,) catalysts was studied under lean conditions using propene as a reducing agent. All supported copper based catalysts were synthesized using the conventional impregnation method. X-ray diffraction analysis was applied to examine the crystalline structure of each synthesized catalyst. The x-ray diffraction patterns showed evidence that coppers were well dispersed on the surface of the catalyst support. The crystalline CuO phase was the major crystallite traced by x-ray diffraction analysis in both catalysts. The ZrO2 has a lower tendency than TiO2, to form crystalline CuO under the same preparation mode. The catalytic performance test using a micro packed bed reactor was conducted for both synthesized catalysts at 1 atm and 300Â°C. The CuZrO2, catalyst showed a better NOx, conversion than CuTiO2. This is particularly due to more crystalline CuO phase formed in CuTiO2 which suppressed the catalytic reduction of NOx, by propene. In this study, it may be concluded that ZrO2, is a good catalyst support for copper loading in the catalytic reduction of NO, by propene.